The Principle of ""Equality of arms"" in criminal procedure under Article 6 of the European convention on Human Rights - Wasek-Wiaderek, Malgorzata (Leuven Law Series, 2000)
The paper deals with one of the significant aspect of fairness in criminal cases, the concept of ""equality of arms"". The considerations focus initially on the analysis of the scope and meaning of the notion of ""equality of arms"" in the case-law of the European Commission and the European Court of Human Rights under Article 6 of the European Convention on Human Rights. The author reviewed the Strasbourg case-law on the concept of